2021
DOI: 10.3390/ijms22063004
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Transplantation during and Post-COVID-19 Pandemic

Abstract: COVID-19 is a major pandemic facing the world today, which has implications on current microbiome-based treatments such as fecal microbiota transplantation (FMT) used for recurrent Clostridioides difficile infections. The bidirectional relationship between the inhabitants of our gut, the gut microbiota, and COVID-19 pathogenesis, as well as the underlying mechanism involved, must be elucidated in order to increase FMT safety and efficacy. In this perspective, we discuss the crucial cross-talk between the gut m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 122 publications
(108 reference statements)
0
22
0
5
Order By: Relevance
“…Diese Hypothese wird durch die Beobachtung gestützt, dass in Autopsiestudien eine hohe Dichte von CD8 + -T-Zellen in der Lunge und anderen Organen beobachtet wurden [25]. Eine weitere Ursache für eine Hyperinflammation oder Autoimmunität können Veränderungen der Mikrobiota des Gastrointestinaltraktes sein [26]. Eine (pro-inflammatorische) Dysbiose ist typisch für COVID-19-Patienten, persistiert über den Krankenhausaufenthalt hinaus und korreliert mit dem Schweregrad der COVID-19-Erkrankungen und einer verlängerten fäkalen SARS-CoV-2-Ausscheidung [27,28].…”
Section: Funktioneller Status Bei Post-/long-covid-patientenunclassified
“…Diese Hypothese wird durch die Beobachtung gestützt, dass in Autopsiestudien eine hohe Dichte von CD8 + -T-Zellen in der Lunge und anderen Organen beobachtet wurden [25]. Eine weitere Ursache für eine Hyperinflammation oder Autoimmunität können Veränderungen der Mikrobiota des Gastrointestinaltraktes sein [26]. Eine (pro-inflammatorische) Dysbiose ist typisch für COVID-19-Patienten, persistiert über den Krankenhausaufenthalt hinaus und korreliert mit dem Schweregrad der COVID-19-Erkrankungen und einer verlängerten fäkalen SARS-CoV-2-Ausscheidung [27,28].…”
Section: Funktioneller Status Bei Post-/long-covid-patientenunclassified
“…With regard to donor and recipient selection for FMT, as the bidirectional gut-lung axis during COVID-19 infection can directly (via ACE2 receptors and gut microbial metabolites) and indirectly (via the immune system) affect the gut and lung, FMT screening protocols are required during and after the COVID-19 pandemic [8]. Another review summarizing donor screening recommendations indicated that diabetes mellitus, prior cardiovascular events, and exposure in clinical healthcare settings should be considered exclusion criteria until more is known about the associations of these conditions with the human gut microbiome [133].…”
Section: Fecal Microbiota Transplantationmentioning
confidence: 99%
“…Moreover, virome-related therapeutic applications to overcome dysbiosis, such as fecal microbiota transplantation (FMT) and phage therapy, have been applied in several clinical trials. Potential adverse effects related to each treatment type should be taken into consideration, and clinical protocols are also required for such applications during the COVID-19 pandemic and post-COVID-19 period [8].…”
Section: Introductionmentioning
confidence: 99%
“…Diskutiert wird, dass das SARS-CoV‑2 in Antigen-präsentierenden Zellen eine „bystander-Aktivierung“ von T‑Zellen gegen Autoantigene auslösen könnte [ 28 ]. Mögliche alternative oder weitere Ursache für eine Hyperinflammation könnten Veränderungen der Mikrobiota des Gastrointestinaltraktes [ 29 ] bzw. eine Dysbiose [ 30 , 31 ] sein.…”
Section: Pathomechanismen – Was Ist Bekanntunclassified